2008
DOI: 10.1186/1472-6963-8-190
|View full text |Cite
|
Sign up to set email alerts
|

Criteria-based audit to improve a district referral system in Malawi: A pilot study

Abstract: Background: To study the feasibility of using criteria-based audit to improve a district referral system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 4 publications
3
28
0
Order By: Relevance
“…Among the major direct causes of maternal death, postpartum hemorrhage may be the most lethal obstetric complication as women can die within a 2‐hour window or less [24,25]. Desired transfer times of 1–2 hours have been adopted by several low‐ and middle‐income countries [26,27]. Given the topography and current distribution of infrastructure in Ethiopia, we adopted 2 hours as the minimum acceptable transfer time in this context of referral between facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Among the major direct causes of maternal death, postpartum hemorrhage may be the most lethal obstetric complication as women can die within a 2‐hour window or less [24,25]. Desired transfer times of 1–2 hours have been adopted by several low‐ and middle‐income countries [26,27]. Given the topography and current distribution of infrastructure in Ethiopia, we adopted 2 hours as the minimum acceptable transfer time in this context of referral between facilities.…”
Section: Methodsmentioning
confidence: 99%
“…A criteria-based audit (CBA) has been used for many years to improve clinical management in developed countries, but has just recently been introduced in developing countries. Recent CBAs in Uganda and Malawi of management of pre-eclampsia and emergency obstetrics demonstrated that it is feasible to improve the quality of obstetric care by using locally available resources [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…An integrated and comprehensive hospital/community based health program is recommended to reduce maternal and child mortality and morbidity in poor‐resources settings (World Health Organization 2005; Murray & Pearson 2006; Kongnyuy et al. 2008; Evjen‐Olsen et al.…”
Section: Introductionmentioning
confidence: 99%